Learning model of basic manipulative movements of throwing and catching: A developmental study through early childhood play - Endang Pratiwi; Hernawan Hernawan; Fahmy Fachrezzy; Norma Anggara; Hikmah Lestari; Aditya Gumantan; Y.Touvan Juni Samodra; M. Adam Mappaompo; Juhannis Juhannis; Albadi Sinulingga (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The importance of learning basic manipulative movements of throwing and catching to be owned by every early childhood because it has benefits and influences on their overall development. This study aims to develop a model of learning basic manipulative movements of throwing and catching in Early Childhood. The type of research adapted is Research and Development (R&D) adopting the Borg & Gall development model which conceptually the research and development steps of this development model include 10 steps namely: 1) research and data collection, 2) planning, 3) development, 4) initial field trial, 5) revision of trial results, 6) second field trial, 7) refinement of field test products, 8) field implementation test, 9) final product refinement, 10) dissemination and implementation. The initial design consisted of 16 game packages. The development stage involved judges, kindergarten teachers, and as samples in small and large scale trials, kindergarten students aged 5-6 years were used. The results of the study resulted in 14 series of games. Based on the effectiveness test, the Ngain value is 75.73%. So that these 14 game models are worth using to develop the throwing and catching skills of children aged 5-6 years. These findings make an important contribution to the development of early childhood education, especially in the context of developing fine motor skills. The learning model developed can be a reference for educators and parents in supporting the development of early childhood manipulative movements through an effective and fun play approach.